P413 A simple scoring tool predicts exposure–response relationship, onset of action, response to interval shortening, and surgical risk with vedolizumab therapy for Crohn's disease. (25th January 2019) - Dulai, P S; Amiot, A; Peyrin-Biroulet, L; Singh, S; Serrero, M; Jairath, V; Filippi, J; Pariente, B; Loftus Jr, E V; Roblin, X; Kane, S; Buisson, A; et al.
Abstract: Background: We previously created and validated a clinical decision support tool (CDST) for predicting response to vedolizumab (VDZ) in Crohn's disease (CD). We now aim to further validate this tool in an additional CD cohort and assess its performance for predicting other health outcomes. Methods: Using GEMINI II data, we explored correlations between VDZ exposure and onset of action across CDST-predicted probability of response groups (low, intermediate, high). The operating properties of the CDST for prediction of clinical remission and onset of action in the GETAID VDZ cohort were evaluated. In the GETAID and VICTORY cohorts, response to dose optimisation was assessed, and in the VICTORY cohort, we assessed the ability of the CDST to predict risk of surgery while on active therapy. Results: A linear relationship was observed between CDST-predicted probability of response groups, VDZ exposure, onset of action, and efficacy in the GEMINI cohort for Week 2 through Week 52 ( p < 0.001). In the GETAID cohort, the CDST predicted clinical remission at Week 14 (AUC 0.68), and a significant difference in speed of onset of action was observed between low- and intermediate–high-probability groups ( p = 0.04). In both the GETAID and VICTORY cohorts, only patients in the low-probability group significantly benefited from shortening of VDZ intervals to Q4 weeks for non-response. In the GETAID cohort, a single infusion at Week 10 for patients in the low-probability group overcame differences in speed of onset of action seen between this group and the intermediate–high-probability group. In the VICTORY cohort, the CDST predicted a 2-fold increase in risk for surgery over 12 months of VDZ therapy among low–intermediate-probability patients compared with high-probability patients (HR 2.06, 95% CI 1.33–3.21). Conclusions: The CD VDZ CDST demonstrated good performance during external validation in the GETAID cohort. This tool was able to prognosticate VDZ exposure-efficacy relationships and speed of onset of action, identify patients who would most benefit from interval shortening for lack of response, and stratify patients at greatest risk for surgery while on active therapy.